Stentless Bioprostheses for Aortic Valve Replacement in Octogenarians: The Influence of Coronary Artery Disease - Ennker, Juergen; Zadeh, Behnam; Pons-Kuehnemann, Joern; Niemann, Bernd; Grieshaber, Philippe; Ennker, Ina C.; Boening, Andreas (The Thoracic and Cardiovascular Surgeon, 2018)
Background We sought to determine the long-term results of stentless biological heart valve replacement in octogenarians to find out whether coronary artery disease or the coronary artery bypass grafting (CABG) procedure itself influences survival in these aged patients.Methods From 4,012 patients undergoing aortic valve replacement (AVR) with a stentless prosthesis (Freestyle, Medtronic) at a single center, 721 patients were older than 80 years. They had a mean age of 83 ±  2 (2,320 patient years), the male/female ratio was 42:58, NYHA (New York Heart Association) class I and II was prevalent in 22.8%, preoperative atrial fibrillation (AF) in 20.6%, coronary artery disease in 56.1%, mitral valve disease in 12.5%, and aortic disease in 3.5%. Follow-up included a total of 11,546 patient years (mean follow-up time: 74 ± 53 months); follow-up mortality data were 96.3% complete.Results In these aged patients, 30-day mortality in the isolated AVR group (10.3%) was similar to that in the AVR + CABG group (13.4%). Although long-term survival (15 years) in the octogenarian population is low (9% in the AVR group and 6% in the AVR + CABG group), it was not different (p = 0.191) between patients with and without coronary artery disease. The stroke rate and the myocardial infarction rate, respectively, in the AVR + CABG group (0.43%/100 patient years and 0.17%/100 patient years) were only insignificantly higher than that in the isolated AVR group (each 0.01%/100 patient years). The actuarial freedom from reoperation was 99% in both the groups.Conclusion Use of the Freestyle stentless valve prosthesis for AVR is feasible also in octogenarians. The existence of coronary artery disease leads to concomitant bypass surgery, but not a higher level of perioperative or long-term mortality.
Keywords: octogenarians; aortic valve replacement; heart valve surgery; stentless bioprosthesis; coronary artery disease